2017
DOI: 10.3382/ps/pex001
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-corrected apparent metabolizable energy values of barley varies by treatment and species

Abstract: The aim of this study was to evaluate the effects of two species of poultry (cockerel and Japanese quail), two levels of enzyme (0 and 0.5 g/kg), and 6 processing methods (control (C), gamma irradiation 25 (GI25), and 50 kGy (GI50), autoclaving (AU), fermentation without lactobacillus (F), and fermentation with lactobacillus (FL)) on the nitrogen-corrected apparent metabolizable energy (AMEn) of barley. In this experiment, each processing method was tested at two levels of enzyme (0 and 0.5 g/kg) in six replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Jakobsen et al [ 39 ] found that fermented RSM had no effect on the content of crude fat and ether extracts, which is in agreement with our results. Insoluble fiber and fat fractions are more resistant to fermentation than their soluble counterparts; protein and digestible starch are preferred as nutrient sources during the fermentation process [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Jakobsen et al [ 39 ] found that fermented RSM had no effect on the content of crude fat and ether extracts, which is in agreement with our results. Insoluble fiber and fat fractions are more resistant to fermentation than their soluble counterparts; protein and digestible starch are preferred as nutrient sources during the fermentation process [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes consumed the insoluble fibers in RSM and produced soluble matters with simple structure; carbohydrate composition was modified as a result of microbial metabolism and, to some extent, due to activation of inherent enzymes in the cereal protein feedstuff [ 43 ]. In a study by Alahyarishahrasb et al [ 29 ], enzyme treatment ( β -glucanase, 0.5 g/kg) barley had significantly higher AMEn values than no enzyme treatment when fed to cockerels. Studies have shown that the addition of enzymes to chicken diets degrades endosperm cell walls, resulting in increased digestibility of nutrients, which otherwise may be encapsulated in the cell structures [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations